Microbial sealants do not decrease surgical site infection for clean-contaminated colorectal procedures - Doorly, M.; Choi, J.; Floyd, A.; Senagore, A. (Techniques in coloproctology, 2015)
Background Surgical site infections (SSI) are costly complications that may cause significant morbidity and increase the cost of care, particularly in colorectal surgery. Microbial sealants (MS) are a new class of wound barriers aimed at decreasing SSI; however, there is only evidence of benefit in clean class 1 procedures. Based on its success in class 1 procedures, we hypothesized that a microbial sealant could reduce the rate of SSI by half for clean-contaminated colorectal procedures (class 2). Methods This was a single institution, multihospital, prospective, randomized study approved by the institutional review board. The primary objective was to determine the rate of SSI when microbial sealant (InteguSeal© Kimberly-Clark) is used compared to control (no microbial sealant). Data collected included: open versus laparoscopy, age, body mass index (BMI), diabetes and morbidity [American Society of Anesthesiologists (ASA) class], hospital readmission, reoperation and wound dehiscence. Enrolled subjects received the same preoperative mechanical bowel preparation with oral antibiotics, operative skin preparation (Chloraprep), Surgical Care Improvement Project guidelines implementation), and postoperative care glycemic control for diabetics. Results A total of 100 subjects were recruited over 15 months (MS-50; no MS-50). The overall incidence of SSI was 12 %, 14 % (7/50) in the MS versus 10 % (5/50) in the no MS group ( p = 0.545). SSI incidence with and without microbial sealant was not significantly different in either the open or the laparoscopic subgroup. Laparoscopy decreased absolute risk of SSI by 16 %. Secondary data (age, BMI, diabetes, ASA) and tertiary data (readmission, reoperation, wound dehiscence) were positively correlated with SSI. Conclusions Microbial sealant as employed in this study did not appear to offer any benefit in a class 2 (clean contaminated) operative procedure when perioperative care is standardized. The relative benefit of laparoscopy was also confirmed but unaffected by use of the microbial sealant.